Investigating the association and causal relationship between restless legs syndrome and essential tremor. (April 2019) - Liao, Calwing; Houle, Gabrielle; He, Qin; Laporte, Alexandre D.; Girard, Simon L.; Dion, Patrick A.; Rouleau, Guy A.
Highlights: Restless legs syndrome not associated or causal in European essential tremor cohort.